Comparison of dry, wet, and microwave ashing methods for the determination of Al, Zn, and Fe in yogurt samples by atomic absorption spectrometry - Yaman, M; Durak, M; Bakirdere, S (Taylor & Francis Inc, 2005)
Digestion methods such as dry and wet ashing and microwave oven were examined at various conditions to determine a rapid, reliable, and simple digestion procedure for yogurt. Digestion by microwave oven was found to be an excellent method in comparison with dry and wet ashing methods when only A1 and Zn in yogurt samples were determined. Iron in this matrix is not completely digested by the microwave oven method at the examined conditions. From the obtained results, yogurt can also be a good source of essential nutrients such as minerals in human diet, especially zinc. Aluminum concentrations in yogurt samples fermented in A1 containers were found to be significantly higher than in plastic containers. Al concentrations of yogurt taken from the bottom of the container were found to be higher than from the center and top of Al containers. The determinations of metals were carried out via an atomic absorption spectrophotometer using calibration curve and standard additions methods. Aluminum concentrations in yogurt samples produced in big production centers were found to be significantly higher than the other yogurt samples produced in-house when plastic containers were used.
Keywords: aluminum; atomic absorption; dry and wet ashing; iron; microwave; yogurt; zinc